Plants from Brazil with Potential Photoprotective Activity: A Review - Paixão, Thiago Portalda; Silva, Margareth Tavares; Andrade, Marcieni Ataide de; Raposo, Nádia Rezende Barbosa; Vieira, José Luiz Fernandes (Pharmacognosy Reviews)
Background: Skin cancer due the solar radiation is an important public health issue in Brazil. Sunscreen formulations protect the skin from the harmful effects of solar radiation. Plants products can have photoprotective compounds that can be incorporated into sunscreen formulations which attend a demand of society for the use of natural compounds in different cosmetics. This review aims to summarize studies that evaluated the photoprotective activity of plants in Brazil in the last ten years. Materials and Methods: A search was conducted in Medline, Scopus, and Embase databases, using the descriptors Brazilian natural products, photoprotection, natural sunscreen, plant extract, and photoprotective activity. Results: A total of 392 manuscripts were retrieved in the databases searched. After applying the criteria of inclusion and exclusion, thirty-six papers were selected, followed by a final screen resulting in twenty-nine. Plant extracts and oils were tested in these studies. The solar photoprotector factor was determined in vitro in most studies. Only three studies were performed in tests in vivo and there were no clinical studies with an adequate sample effort. Conclusion: Several plant extracts demonstrated promising solar photoprotective activity in vitro, such as Erythrina velutina, Dalbergia monetaria, and Garcinia brasiliensis, which recommend complementary studies for use in sunscreens formulations as most of the studies with Brazilian plants were focused on preliminary analyses in the last decade.
Keywords: Brazilian natural products; Photoprotection; Solar protection factor; Plants